Loss of visceral adipose tissue precedes subcutaneous adipose tissue and associates with n-6 fatty acid content. Issue 6 (December 2016) - Ebadi, Maryam; Baracos, Vickie E.; Bathe, Oliver F.; Robinson, Lindsay E.; Mazurak, Vera C.
Summary: Background & aim: During cancer development, fat loss occurs in most cancer patients. Characterization of the behavior of fat loss from visceral (VAT) and subcutaneous adipose tissue (SAT) depots has not been established. The first objective of this study was to assess the intensity and time course of changes in VAT and SAT depots of advanced cancer patients in the year preceding death. Secondly, this study explored the differences in adipokine content and fatty acid composition between VAT and SAT depots and in relation to changes in fat mass. Methods: Longitudinal quantitative analyses of computed tomography images was conducted to define changes in adipose tissue cross sectional areas in fat depots in advanced colorectal and cholangiocarcinoma cancer patients (n = 46) at mean time points corresponding to 9, 6, 3 and 1 month before death. Proportions of adipose tissue fatty acid and adipokine content were characterized in a second cohort of advanced colorectal cancer patients (n = 16). Results: On average, loss of total adipose tissue (TAT) happens at all time intervals but there is an elevation in the intensity of loss close to death. Nine months from death, 42% of patients were losing fat (Mean TAT cross sectional area change = −0.2 ± 13 cm 2 ) whereas within one month from death, fat wasting was observed in 78% of patients (−60.1 ± 9.2 cm 2, P = 0.001). However, loss of TAT did not reflect changes in VAT and SAT in the same direction or intensity. Intensity of VAT loss remains constant throughout the disease progression whereas SAT is more likely to be gained further way from death. Nine month prior to death, mean change in cross sectional area of VAT was −7.9 ± 6.8 cm 2 whereas, mean change in CSA of SAT was 7.4 ± 7.7 cm 2 (p = 0.03). One month before death, mean VAT and SAT absolute changes were −24.5 ± 4.9 cm 2 and -34.5 ± 5.2 cm 2, respectively (p = 0.05). Moreover, fat losing patients had higher proportions of polyunsaturated fatty acids, especially n-6 fatty acids, in VAT compared to patients who were gaining fat (mean = 15.4% in losing group vs. 13.4% in gaining group; p = 0.03). VAT contained more monocyte chemoattractant protein-1 than SAT, whereas leptin levels were higher in SAT. Conclusions: Further from death, VAT and SAT behave differently whereas close to death, accelerated loss occurs in both depots. These differences are further characterized by differences in fatty acid composition and adipokine levels.